2020
DOI: 10.3390/nu13010129
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of α-Tocopherol, α-Tocopherol Acetate, and α-Tocopheryl Polyethylene Glycol Succinate 1000 Absorption by Caco-2 TC7 Intestinal Cells

Abstract: (1) Background: vitamin E is often supplemented in the form of tocopherol acetate, but it has poor bioavailability and can fail to correct blood tocopherol concentrations in some patients with severe cholestasis. In this context, α-tocopheryl polyethylene glycol succinate 1000 (TPGS) has been of value, but very little is known about the mechanisms of its absorption. The aim of our work was to evaluate the mechanisms of absorption/secretion of TPGS compared to tocopherol acetate (TAC) and α-tocopherol by human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…The fact that we observed a lower α-tocopherol secretion in MTTP -KO clones than in SAR1B -KO clones is consistent with clinical observations, as FHBL-SD1 patients present more severe vitamin E deficiency than FHBL-SD3 patients [ 40 ]. Our results are also consistent with a previous cell-based study designed to characterize the absorption of free tocopherol, TAC and TPGS [ 13 ]. This previous study also reported a basolateral secretion of TAC in its intact form (202 pmol/well after 24 h of incubation).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The fact that we observed a lower α-tocopherol secretion in MTTP -KO clones than in SAR1B -KO clones is consistent with clinical observations, as FHBL-SD1 patients present more severe vitamin E deficiency than FHBL-SD3 patients [ 40 ]. Our results are also consistent with a previous cell-based study designed to characterize the absorption of free tocopherol, TAC and TPGS [ 13 ]. This previous study also reported a basolateral secretion of TAC in its intact form (202 pmol/well after 24 h of incubation).…”
Section: Discussionsupporting
confidence: 92%
“…We then characterized the secretion of α-tocopherol, TAC and TPGS by wild-type Caco-2 cells compared to KO clones. Alpha-tocopherol is one of the main dietary forms of vitamin E. In clinical nutrition, vitamin E deficiency is usually treated with oral α-tocopherol-acetate (TAC) to protect the phenol group against oxidation [ 13 , 39 ]. Due to the poor bioavailability of TAC and because of the interest in treating patients with Monogenic Hypobetalipoproteinemia Disorders with TPGS, a drinkable form of tocopherol, we characterized and compared the uptake and secretion of α-tocopherol, TAC and TPGS in the different clones.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations